The Effect of Stage of Estrous Cycle on The Development of Bovine Embryo Matured and Fertilized in Vitro - I. Djuwita; B. Purwantara; Y. Sukra; M. Fahrudin; A. Winarto (Media Veteriner, 1996)
The objective ofthis study is to examine the effect of stage of estrous cycle on in vitro development of bovine embryo matured and fertilized in vitro. Cow ovaries were collected from slaughter house and were kept in a physiological solution. Oocytes were aspirated using GI8 neddle connected to 10 mL syringe containing phosphate buffer saline (PBS). After being washed, oocytes were matured in vitro in Tissue Culture Medium (TCM) 199 a physiological in 5% CO2 incubator at 39°C for 20-22 hours. In vitro fertilization was done in BO (Brackett and Oliphant) solution for 8 hrs, using frozen semen. Embryos were further cultured in either TCM-199 supplemented with 5% cow superovulated serum or chemically defined-serum free medium. If ovaries were classified due to their estrous stages, i.e. luteal and follicular, both cleavage (fertilization) and development rates did not show any differences (p < 0,5) in both treatment. The cleavage rate of oocytes collected from the follicular and luteal stages were 75.0% and 75.6%. respectively even though was lower if compared to that withaout classification (83.5 %). The development rate were 20,0% and 23,0%, higher, compare to that without classification, i.e. 13.0%. Nevertheless, if chemically defined-serum free medium was used, the two treatments showed differences (p < 0,5) in both cleavage and development rates. The ratio between luteal and follicular stages were 68,0% : 80,0% and 53,6%: 65,7% for cleavage and development rates, respectively.